(untitled) (Journal of Global Accounting, 2024)
This study ascertained the effect of cash management on the financial performance of industrial goods firms in Nigeria. The specific objectives of the study are to: determine the effect of cash and cash equivalent on the return on assets of industrial goods firms in Nigeria; and evaluate the extent to which cash turnover affects the return on assets of industrial goods firms in Nigeria. Research questions and hypotheses are formulated in line with the objectives of the study. Ex-Post Facto research design was adopted. The population of the study was consisting of twelve (12) industrial goods in Nigeria. Data were extracted from the companies of the study annual reports and accounts from 2013 to 2022. Analysis was carried out with descriptive statistics and regression analysis. The study revealed that there is a significant effect between cash and cash equivalent and return on assets of industrial goods firms in Nigeria. Also there is a significant effect between cash turnover and return on assets of industrial goods firms in Nigeria. The study therefore recommended among others that since the study found that cash and cash equivalent has a significant effect, therefore, management should endeavour to maintain the optimum balance between too much cash and too little cash in an organization to ensure its smooth operation and performance.